How Could Static Telepathology Improve Diagnosis in Neuropathology? - Myriam Remmelinck; M. Beatriz S. Lopes; Nathalie Nagy; Sandrine Rorive; Katja Rombaut; Christine Decaestecker; Robert Kiss; Isabelle Salmon (Analytical Cellular Pathology)
The present paper reports our experience with, and our opinion of static telepathology as applied to neuropathology by means of the PHAROS acquisition system and conventional telephone data transmission (modem). The classical procedure of expert consultation based on surface mailing of histological slides is routinely performed, especially in highly specialized fields of pathology. Telepathology is an easy means of sharing scientific expertise at international level and could thus improve diagnosis particularly in neuropathology, where certain tumor types are very rare and complex to diagnose. Dynamic telepathology allows the referring pathologist to capture by himself images supporting their diagnosis. Using static telepathology the pathologist could be limited in diagnosis by problems in fields selection.